HUBUNGAN ANTARA POLA PERHATIAN VISUAL DAN KECEPATAN MENGIDENTIFIKASI HURUF PADA ANAK BERKEBUTUHAN KHUSUS DI SDN SUNGAI LULUT 2 - Ahmad Nasir; Gina Kafila Ardana; I Kadek Wiana; Melsy Nor Wedya; Raisya; Ahmad Suriansyah; Maimunah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem of reading difficulties in children with special needs is significant, especially related to the ability to recognize and identify letters quickly and accurately. This barrier is often caused by limitations in visual attention patterns that affect the process of learning to read. This study aims to analyze the relationship between visual attention patterns and letter identification speed in children with special needs at SDN Sungai Lulut 2. The method used was quantitative descriptive with data collection through observation, reading tests, interviews, and document studies on two students with different characteristics. Data analysis was carried out by calculating the average score and interpreting the pattern of relationships between variables. The results showed that good visual attention patterns were associated with higher letter recognition speeds. Tournament-based learning methods have been proven to be effective in improving children's visual focus and learning motivation. Research implications of the importance of learning methods and varied visual media in inclusive education to improve the literacy of children with special needs. With the right approach, these children can improve their reading skills and retain attention better.